An Analysis of Students' Errors in Writing Descriptive - Sri Puji Rahayu; Dyah Kusumastuti (Universitas Muhammadiyah Surabaya, 2023)
This research is to find out the research of the students writing descriptive text. Researchers used the descriptive qualitative method. This research was conducted at a private high school in Cilacap, Central Java, Indonesia with a population of 85 students consisting of 12th grade students divided into 4 classes. The researchers used simple random sampling with a total sample of 20 students. Written test instruments were used in this study and interviews were used to find out why students made many mistakes in writing. There were several types of errors found in students’ writing, namely omission of 92 or 54%. The occurrence of addition is 28 or about 16%. The occurrence of misformation errors is 47 or about 28%. The occurence of misordering errors is 4 or about 2%.